Role of K3-xHxPW12O40 as a Catalyst in Selective Catalysis of Methylamine Synthesis from Ammonia and Methanol - Nasikin, Mohammad (UI Scholars Hub, 2003)
Role of K3-xHxPW12O40 as a Catalyst in Selective Catalysis of Methylamine Synthesis from Ammonia and Methanol. Synthesize of methylamine from methanol and ammonia was studied in this research work using a partially potassium heteropoly salt (K3-xHxPW12O40 abbreviated as KPW) as a catalyst. KPW was prepared from heteropoly salt and potassium carbonate by using ion exchange method. The reaction was conducted at 600 800K and at the atmospheric pressure. Reactor used was a continue flow reactor with W/F=0,1 0,9g-kat.mnt./cc.Concentration of reactants and products were analyzed by gas chromathography while catalyst structure was observed by XRD (X-ray diffraction). Isothermal adsorption method was used for determining catalyst pore size. The result showed that ion exchange between H ion in zeolit with K ion produced potassium heteropoly salt that caused the change of interstitial space. The change of interstitial space was observed by the change of the lattice constant of the catalyst crystal. Trimethylamine(TMA) has molecule size smaller than catalyst pore size but bigger than molecular size of Dimethylamine (DMA) and Monimethylamine (MMA). This phenomenon caused the suppression of TMA formation. KPW has a rigid crystal structure and stabil during reaction. On the other hand, crystal structure of a non selective catalyst (NH4)3PW12O40 was not rigid and its pore size is easy to change depending on the product molecule size.